-0.67(x+1)=6

Simple and best practice solution for -0.67(x+1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.67(x+1)=6 equation:


Simplifying
-0.67(x + 1) = 6

Reorder the terms:
-0.67(1 + x) = 6
(1 * -0.67 + x * -0.67) = 6
(-0.67 + -0.67x) = 6

Solving
-0.67 + -0.67x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.67' to each side of the equation.
-0.67 + 0.67 + -0.67x = 6 + 0.67

Combine like terms: -0.67 + 0.67 = 0.00
0.00 + -0.67x = 6 + 0.67
-0.67x = 6 + 0.67

Combine like terms: 6 + 0.67 = 6.67
-0.67x = 6.67

Divide each side by '-0.67'.
x = -9.955223881

Simplifying
x = -9.955223881

See similar equations:

| 4(a-5)+6=2(a-6) | | 8x-3=7(x+5)+4 | | -5s=1.25 | | 3/4x-1=7/5 | | 9x-2=6x+43 | | -3=5(z+7) | | 3X+8Y=30 | | 24=-8y | | 4x^2-19x+24=-2x+9 | | 4x^2-16x+24=-2x+9 | | 12(r-2)=0 | | (8r-64)/4 | | 8r-64/4 | | (X^3+9x^2+7x-24)/(x-2) | | (7/4)x=56 | | 9/1-27/7 | | .5=.5555 | | 12x+3+4x=48 | | 4ax+5ab= | | 6x^5+10x^4-56x^3=0 | | 36/7+X=9 | | 50=-7E-05x^2+0.0164x+0.021 | | 3(6+2y)y=1 | | 3(-8)+4y=20 | | -2(x-6)= | | y=-7E-05x^2+0.0164x+0.021 | | 10x^2+9x-3=0 | | =4a+10b-7a+4b | | 18-15^2+36-32^2/55-50 | | 5*x-4=30 | | 2x=1#5=x | | b(x-d)=c(x-d) |

Equations solver categories